Eruption chronology of the first deciduous teeth in children born prematurely with birth weight less than 1500g - Pedro Garcia F. Neto; Mario Cicero Falcao (Sociedade de Pediatria de São Paulo, 2014)
Objective: To describe the eruption chronology of the first deciduous teeth in premature infants with birth weight less than 1500g and to compare it according to gender and nutritional status at birth. Methods: Longitudinal study including 40 low birth weight premature infants of both genders. The tooth was considered erupted when the crown went through the gum and became part of the oral environment. The comparison of the eruption chronology in relation to gender and among children appropriate or small for gestational age was done by Student's t-test, being significant p<0.05. Results: The eruption of the first tooth (teeth) occurred, on average, with 11.0±2.1 months of chronological age and with 9.6±1.9 months corrected for prematurity. The first erupted teeth were the lower central incisors. The average eruption for males was 9.7±1.9 and, for females, 9.5±1.9 months, both corrected for prematurity (p=0.98). The average eruption in children with birth weight appropriate for gestational age was 10.1±1.4 months; for small for gestational age, it was 9.4±2.2, also corrected for prematurity (p=0.07). Conclusions: The average eruption age of the first teeth, corrected for prematurity, was 9.6 months. Sex and nutritional status at birth did not change the eruption chronology.